Pengaruh Kualitas Sarana dan Prasarana terhadap Minat Belajar Siswa dalam Pembelajaran Pendidikan Agama Islam - Kartika, Sinta; Husni, Husni; Millah, Saepul (Jurnal Penelitian Pendidikan Islam, 2019)
This research article found that (1) the quality of facilities and infrastructure at SMK AL Huda Turalak has an average rate of 46.83 classified as medium clarification because it is in the range of scores between 46.15 to 52.00; (2) the learning interest of SMK AL Huda Turalak students has an average of 47.32, it is included in the medium category because it is in the range of scores between 46.15 to 52.00; and (3) there is an influence between the quality of facilities and infrastructure on students' interest in learning at Al-Huda Turalak Vocational School. This is obtained from the analysis of SPSS 20, from the analysis it is known that the sig (2-tailed) value of 0.001 <0.05, then H0 is rejected and the correlation coefficient value of 0.405 is classified as moderate interpretation. From the data above shows that there is an influence between the quality of facilities and infrastructure on students' interest in learning PAI at Al-Huda Turalak Vocational School. Then the correlation is r = 0.405 or 40.5%, and the number lies in the number 0.410-0.60, meaning the correlation between the X variable and the Y variable is moderate. While 59.5% of student interest is influenced by other factors.